Cricoarytenoid Rheumatoid Arthritis: An Important Consideration in Aggressive Lesions of the Larynx - Chen, Joseph J.; Branstetter, Barton F.; Myers, Eugene N. (American Journal of Neuroradiology, 2005)
Summary: The most frequent cause of an aggressive mass in the larynx is squamous cell carcinoma (SCC). Rheumatoid arthritis is known to affect the larynx but does not usually produce an aggressive mass. We present a case of rheumatoid arthritis in a 63-year-old woman who presented with acute upper airway obstruction. On CT scans, an erosive mass on the right cricoid cartilage with significant destruction of the surrounding structures was presumed to be an aggressive SCC. Surgical biopsies revealed rheumatoid arthritis of the cricoarytenoid joint. When a patient with rheumatoid arthritis presents with a mass in the larynx, cricoarytenoid rheumatoid arthritis should be ruled out even in the face of an aggressive lesion appearance at CT.